There's a frog in my throat! 440 animal sayings a little bird told me - Pat Street (U.S.A Scholastic Inc., 2003)
Explains various animal expressions that employ similes, metaphors, idioms, and proverbs.
Keywords: Read Aloud Non Fiction + CIrcle time - Language Concept -- Read Aloud Non Fiction + CIrcle time - Language Concept; Circle Time Book - Language Mechanics -- Circle Time Book - Language Mechanics